Historical Dimensions of the Role of Women in the Ayyubid State (567-657 AH/1171-1260 AD) - Zainal, Prof.Dr.Aras Friq; Ahmed, Diman Hasib (Sulaimani Journal for Humanities, 2026)
Historical dimensions generally support the role of women in the different stages of the Ayyubid state between the peoples (567-648 AH/1171-1250 AD). The Ayyubid state and its rule were based on a largely religious basis, and the Ayyubids were also expelled from the Roman Empire because of their skills, sales and gifts to Egypt and Syria He reached the rule of a large geographical area during the reign of his great leader Yousef bin Najmuddin. Bin Ayyub bin Shad, the well-known wife of Sultan Salah al-Din al-Ayyubi. Supporting the historical distance (religious, social, political and administrative) away from all the prominent women of the Ayyubid state such as (Esmah Khatun), (Rabia Khatun) and (St. Al-Sham). For example, the establishment of the state, which is one of the upper layers in society and politics, and the political and administrative dimensions more support for the role of women in the second phase For the state it was a change in the history of the state in the peoples (589-635 AH/1193-1249 AD). Beginning with political marriage, despite the personal and emotional dimensions, supports other women such as Suda. In addition to the stability of political and administrative history, the personal dimension also supports the role of women and their leadership through the weakness of the state and its students, among the peoples (635-648 AH/1249-1258 AD). It is named after the third generation of Ayyubids, which is related to the role of Zafa Khatun and the role of the tree, and the religious side of the tree, which is now the official role of the tree, is the reason Finally the Ayyubid state. As these dimensions, alongside the economic and religious dimensions, contributed in a special way to the role of women in the civilization of the Ayyubid state.